2014
DOI: 10.1016/j.meatsci.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of red and processed meat in colorectal cancer development: a perspective

Abstract: This paper is based on a workshop held in Oslo, Norway in November 2013, in which experts discussed how to reach consensus on the healthiness of red and processed meat. Recent nutritional recommendations include reducing intake of red and processed meat to reduce cancer risk, in particular colorectal cancer (CRC). Epidemiological and mechanistic data on associations between red and processed meat intake and CRC are inconsistent and underlying mechanisms are unclear. There is a need for further studies on diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 154 publications
3
111
0
5
Order By: Relevance
“…Recently, in curing application researchers were investigate finding a good combination with sodium nitrite or decrease their residual in finished meat products (Honikel, 2008;Dostindjer et al, 2014). Furthermore, increasing in consumer demands on the natural food products support this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in curing application researchers were investigate finding a good combination with sodium nitrite or decrease their residual in finished meat products (Honikel, 2008;Dostindjer et al, 2014). Furthermore, increasing in consumer demands on the natural food products support this approach.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most studies [3][4][5] have investigated the effect of specific foods, food groups, or nutrients. Consumption of vegetables and dairy products has been related to a decreased colorectal cancer risk, whereas consumption of red and processed meat has been associated with an increased Risk.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a preventive diet might involve limitation or avoidance of red or processed meats and consumption of white meat and fish 25 . Although epidemiologic studies have observed a strong association between meat intake The U.S. rates were calculated using 5-year age-specific Surveillance, Epidemiology, and End Results data for 1995-1999 and the age structure of the U.S. population during the same years 7 (used with permission from the Archives of Iranian Medicine).…”
Section: Crc and Red And Processed Meat Consumption By Iraniansmentioning
confidence: 99%